2015
DOI: 10.1121/1.4916267
|View full text |Cite
|
Sign up to set email alerts
|

Passive probing of the sound fixing and ranging channel with hydro-acoustic observations from ridge earthquakes

Abstract: The International Monitoring System includes a hydro-acoustic part to verify the Comprehensive Nuclear-Test-Ban Treaty. Besides explosive signals, monitoring stations also detect acoustic waves from earthquakes that travel through the SOund Fixing And Ranging (SOFAR) channel. The travel times of such detections are listed in the Reviewed Event Bulletin, which is statistically evaluated for the stations located in the Pacific, Indian, and Atlantic Oceans. The celerities of ridge earthquakes are calculated to bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Derived sound speed values average at 1,474 m/s and are well within two standard deviations (±14 m/s) of the nominal estimate of 1,481 m/s (Figure d). The offset could be explained by the movement of the hydrophone moorings due to deep ocean currents as well as local variations in ocean temperature, and hence, sound speed across the array (e.g., Evers & Snellen, ).…”
Section: Hydrophone Triplet Data and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Derived sound speed values average at 1,474 m/s and are well within two standard deviations (±14 m/s) of the nominal estimate of 1,481 m/s (Figure d). The offset could be explained by the movement of the hydrophone moorings due to deep ocean currents as well as local variations in ocean temperature, and hence, sound speed across the array (e.g., Evers & Snellen, ).…”
Section: Hydrophone Triplet Data and Processingmentioning
confidence: 99%
“…Long‐range propagation of low‐frequency underwater sound phases is a key feature of the hydroacoustic waveform component of the International Monitoring System (IMS). As part of the verification regime for the Comprehensive Nuclear‐Test‐Ban Treaty (CTBT) of 1996, the objective of the IMS hydrophone network is to globally detect underwater nuclear explosions, but the comprehensive installation also enables the study of natural phenomena, including among others, earthquake rupture propagation (Guilbert et al, ; Tolstoy & Bohnenstiehl, ), tsunami signals (Matsumoto et al, ), ocean acoustic propagation (Evers & Snellen, ), and marine mammal vocalization (Le Bras et al, ; Ward et al, ). A total of 11 hydroacoustic receiver sites are in operation worldwide, six of which are hydrophone triplet arrays, typically deployed at remote ocean islands and near the SOFAR channel axis.…”
Section: Introductionmentioning
confidence: 99%
“…A study with deterministic transient signals from earthquakes has already shown the ability to probe the deep ocean's temperature with hydroacoustic recordings from the IMS (Evers & Snellen 2015). In this study, it is aimed to passively retrieve the deep ocean temperature from the ambient acoustic noise field.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned sources confine the dominant sources of the hydroacoustic network's ambient noise field. Recent studies have shown the potential of passive hydroacoustic thermometry in the SOFAR channel using traveltime variations of ridge earthquakes (Evers & Snellen 2015) and by crosscorrelating ambient signals recorded at two distinct IMS arrays, H10N and H10S, located near Ascension Island in the South Atlantic Ocean (Woolfe et al 2015;Evers et al 2017).…”
Section: Introductionmentioning
confidence: 99%